KEPEMIMPINAN KEPALA DESA DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA KAREGESAN KEC. KAUDITAN KAB. MINUT (Satu Studi Di Desa Karegesan Kecamatan Kauditan Kabupaten Minahasa Utara) - Weenas, Nanda Agnesya; Lengkong, Daicy; Mambo, Rully (Sam Ratulangi University, 2015)
The figure of the professional and leadership required to properly master the job exceeds theaverage of existing employees, as well as having high moral commitment on its work in accordancewith the code of ethics profession as a leader. Leader / Leadership is a subject that should encouragecommunity participation in development through the demands and suggestions and effective decisionmakingto the people to achieve development goals.In Law Number 32 Year 2004 on Regional Government as changes in Law No. 12 Year 2008 andGovernment Regulation No. 73 of 2005 on Regional, village, and village, chapter 4, explained thatreferred to in has the task of conducting the affairs of government and community development. Inaddition to the task as intended, implementing government affairs delegated by the Regent / Mayor.Followed up by Regulation Karegesan Village district. Kauditan Kab. Minut No. 21 of 2004 which wassubsequently replaced by the regional regulation and Village No. 11 of 2008 in the Law on VillageGovernment Amendment Latest: Government Regulation (PP) No. 43 of 2014 on the Regulation onthe Implementation of Law No. 6 of 2014 on the village, a variety of things set in GovernmentRegulation No. 43 Year 2014 concerning the Implementation Regulations of Law No. 6 of 2014 on thevillage.One village chief authority is to foster the life of the villagers. Coaching is one very importantelement in the process of infrastructure development for the community, be it guidance for the villageand for the people. The purpose of the Infrastructure Development is better to change the lives ofvillagers. In practice, the village chief to use the concept of awareness and willingness of the peoplethemselves to participate and assist the government in rural development better.Keywords: Leadership, Village Head, Infrastructure Development